2022
DOI: 10.3390/nu14173527
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Choices Five-Level Criteria and Nutri-Score: Alignment with the Dutch Food-Based Dietary Guidelines

Abstract: The current food environment in the Netherlands is considered obesogenic. Eighty percent of the products in supermarkets are unhealthy. The Wheel of Five is the well-established, science-based Dutch food-based dietary guideline (FBDG) developed to stimulate healthier choices. In addition, simple directions on food packaging, such as front-of-package (FOP) health logos, could also be helpful. However, these tools should be in line with each other, in order not to confuse the consumer. To study this, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This model was originally developed for limiting the marketing of unhealthy foods to children and does not incorporate some recent dietary recommendations, such as reducing the intake of red meat and the importance of whole grains (Blomhoff et al., 2023; Willett et al., 2019). Alternative approach would be to use country‐specific FBDG (Huybers & Roodenburg, 2023; Konings et al., 2022), which are in Slovenia and not defined to a level that would allow meaningful comparison. Further research should also focus on the assessment of the evolution of NS using country‐specific FBDG where available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This model was originally developed for limiting the marketing of unhealthy foods to children and does not incorporate some recent dietary recommendations, such as reducing the intake of red meat and the importance of whole grains (Blomhoff et al., 2023; Willett et al., 2019). Alternative approach would be to use country‐specific FBDG (Huybers & Roodenburg, 2023; Konings et al., 2022), which are in Slovenia and not defined to a level that would allow meaningful comparison. Further research should also focus on the assessment of the evolution of NS using country‐specific FBDG where available.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review captured 30 papers: 24 original research (Angelino et al, 2023;Braesco et al, 2022;Bryngelsson et al, 2022;Cutroneo et al, 2022;de las Heras-Delgado et al, 2023;Dickie et al, 2022;Ebner et al, 2022;Fedde et al, 2022;Ferreiro et al, 2021;Fialon et al, 2022;Hafner & Pravst, 2021, 2023Huybers & Roodenburg, 2023;Katsouri et al, 2021;Kissock et al, 2022;Konings et al, 2022;Panczyk et al, 2023;Pitt et al, 2023;Pointke & Pawelzik, 2022;Rodriguez-Martin et al, 2023;Septia Irawan et al, 2022;Stiletto & Trestini, 2022;Borg et al, 2021;Valenzuela et al, 2022), 3 communication/correspondence (Carruba et al, 2022;Drewnowski et al, 2021;Hau & Lange, 2023), and 3 review papers (Peonides et al, 2022;van der Bend et al, 2022;Włodarek & Dobrowolski, 2022), originating from 19 countries (including 12 EU member states). The list of reported limitations (n = 20), their connections, and the numbers of mentions are presented in Figure 2.…”
Section: Reported Limitations Of Ns2021 Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the authors did not utilize the Nutri-Score 2022 algorithm. A 2022 study by Konings et al [ 36 ] compared how well two FOPNLs—the Choices five-level criteria, and the Nutri-Score—aligned to current Dutch food-based dietary guidelines. The authors found that the Choices five-level criteria aligned more closely with the food-based dietary guidelines, noting that many discrepancies were found between the Nutri-Score and the guidelines.…”
Section: Discussionmentioning
confidence: 99%